Controlling joint instability after anterior cruciate ligament transection inhibits transforming growth factor-beta-mediated osteophyte formation. Issue 8 (August 2019) - Murata, K.; Kokubun, T.; Onitsuka, K.; Oka, Y.; Kano, T.; Morishita, Y.; Ozone, K.; Kuwabara, N.; Nishimoto, J.; Isho, T.; Takayanagi, K.; Kanemura, N.
Summary: Objective: Abnormal joint instability contributes to cartilage damage and osteophyte formation. We investigated whether controlling joint instability inhibited chronic synovial membrane inflammation and delayed osteophyte formation and examined the role of transforming growth factor-beta (TGF-β) signaling in the associated mechanism. Design: Rats ( n = 94) underwent anterior cruciate ligament (ACL) transection. Anterior tibial instability was either controlled (CAM group) or allowed to continue (SHAM group). At 2, 4, and 8 weeks after surgery, radiologic, histopathologic, immunohistochemical, immunofluorescent, and enzyme-linked immunosorbent assay examinations were performed to evaluate osteophyte formation and TGF-β signaling. Results: Joint instability increased cartilage degeneration score and osteophyte formation, and cell hyperplasia and proliferation and synovial thickening were observed in the synovial membrane. Major findings were increased TGF-β expression and Smad2/3 following TGF-β phosphorylation in synovial membarene, articular cartilage, and the posterior tibial growth plate (TGF-β expression using ELISA: 4 weeks; P = 0.009, 95% CI [260.1–1340.0]) (p-Smad2/3 expression density: 4 weeks; P = 0.024, 95% CI [1.67–18.27], 8 weeks; P = 0.034, 95% CI [1.25–25.34]). However, bone morphogenetic protein (BMP)-2 and Smad1/5/8 levels were not difference between the SHAM model and the CAM model. Conclusions: This study showed that the difference between anterior tibial instability caused a change in the expression level of TGF in the posterior tibia and synovial membrane, and the reaction might be consequently involved in osteophyte formation.